The Bumiputera Policy and Nation Building - Cheah Boon Kheng, (Kajian Malaysia, 2003)
Although not used explicitly in the Malaysian Constitution, the term bumiputera is in common usage, and in some cases, the words bumiputera and/or "native" are used interchangeable. Politically, the usage of the term is complex and sometimes creates confusion, as clearly pointed out in a recent political science study: "The definition of bumiputera is 'sons of the soil', and hence it refers to the indigenous peoples of the country, which include Malays as well as aborigines and the natives of Sabah and Sarawak. However, in Malaysian politics, the terms bumiputera and 'Malay' (a Malay is defined as a Muslim who habitually speaks Malay and follows Malay customs and norms) are often used interchangeably, which implies that they mean the same thing. Obviously, they do not. Many of the nonMalay bumiputera from Sabah and Sarawak are not Muslims, and hence do not fit the definition of 'Malay'. Neither do the orang asli (literally, the original people), the aborigines of the Malay peninsula, who are mostly animists. Conversely, some Malays are actually immigrants from Indonesia, and are hence, not real bumiputera. The reason for all the confusion, deliberately fostered in part by the government has to do with political expedienc